Study of mortality risk factors and outcomes in COVID-19 patients at a tertiary care hospital in West Bengal, India (Bangladesh Critical Care Journal, 2023)
Background: The risk of mortality is high in Coronavirus disease-19 (COVID-19)patients. The management of COVID-19 patients may be aided by the identification of variables associated with mortality. The aim of the study was to ascertain the outcomes and mortality risk factors in COVID-19 patients at a tertiary care facility in West Bengal, India.Method: A total of 94 patients with moderate to severe symptoms of COVID-19 were included in this observational descriptive study from April 2021 to June 2021. The patients with moderate to severe infection diagnosed by Indian Council of Medical Research (ICMR) guidelines admitted to the hospital, and those willing to participate in the study, were included. Those with mild symptoms and who refused to participate were excluded from the study. The severity of patient condition was determined by Ministry of Health & Family Welfare (MoHFW) guidelines. Informed consent has been obtained from patients. Data was analyzed by Microsoft® Excel workbook 2007 into SPSS v 21.0 (IBM, USA).Results: Fifty-four percent of the patients had moderate, and 45.7% had severe infections. In-hospital mortality was 41.5% among moderate to severe infected COVID 19 positive patients. Non-survivors have significantly higher levels of neutrophils to lymphocyte ratio (NLR), blood urea, and sodium levels in comparison with survivors (P